Patients' and family members' views on pacemaker reuse: An international survey. (29th January 2022) - Hughey, Andrew B.; Muthappan, Palaniappan; Badin, Auroa; Baman, Timir; Baig‐Ansari, Naila; Jawed, Fayez; Khan, Abdul B.; Jiang, Qingmei; Hughey, Katherine L.; Toruño, Rolando J.; Machado, Christian; Refaat, Marwan M.; et al.
Abstract: Introduction: The reuse of cardiac implantable electronic devices may help increase access to these therapies in low‐ and middle‐income countries (LMICs). No published data exist regarding the views of patients and family members in LMICs regarding this practice. Methods and Results: An article questionnaire eliciting attitudes regarding pacemaker reuse was administered to ambulatory adult patients and patients' family members at outpatient clinics at Centro Nacional Cardiologia in Managua, Nicaragua, Indus Hospital in Karachi, Pakistan, Hospital Carlos Andrade Marín, and Hospital Eugenio Espejo in Quito, Ecuador, and American University of Beirut Medical Center in Beirut, Lebanon. There were 945 responses (Nicaragua – 100; Pakistan – 493; Ecuador – 252; and Lebanon – 100). A majority of respondents agreed or strongly agreed that they would be willing to accept a reused pacemaker if risks were similar to a new device (707, 75%), if there were a higher risk of device failure compared with a new device (584, 70%), or if there were a higher risk of infection compared to a new device (458, 56%). A large majority would be willing to donate their own pacemaker at the time of their death (884, 96%) or the device of a family member (805, 93%). Respondents who were unable to afford a new device were more likely to be willing to accept a reused device (79% vs. 63%, p  < .001). Conclusions: Patients and their family members support the concept of pacemaker reuse for patients who cannot afford new devices.